Incidence of intravenous drug incompatibilities in intensive care units - Machotka, Ondrej; Manak, Jan; Kubena, Ales; Vlcek, Jiri (Biomedical papers, 2015)
Aims: Drug incompatibilities are relatively common in inpatients and this may result in increased morbidity/mortality as well as add to costs. The aim of this 12 month study was to identify real incidences of drug incompatibilities in intravenous lines in critically ill patients in two intensive care units (ICUs).Methods: A prospective cross sectional study of 82 patients in 2 ICUs, one medical and one surgical in a 1500-bed university hospital. One monitor carried out observations during busy hours with frequent drug administration. Patients included in both ICUs were those receiving at least two different intravenous drugs.Results: 6.82% and 2.16% of drug pairs were found to be incompatible in the two ICUs respectively. Among the most frequent incompatible drugs found were insulin, ranitidine and furosemide.Conclusions: The study showed that a significant number of drug incompatibilities occur in both medical and surgical ICUs. It follows that the incidence of incompatibilities could be diminished by adhering to a few simple rules for medication administration, following by recommendations for multiple lumen catheter use. Future prospective studies should demonstrate the effect of applying these policies in practice.
Keywords: medical error; medical; medication safety; drug administration; drug incompatibilities; intensive care units